2022
DOI: 10.3390/app12147124
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Recognition Based on Non-Contact Radar Data and Improved PCA Method

Abstract: Human activity recognition (HAR) can effectively improve the safety of the elderly at home. However, non-contact millimeter-wave radar data on the activities of the elderly is often challenging to collect, making it difficult to effectively improve the accuracy of neural networks for HAR. We addressed this problem by proposing a method that combines the improved principal component analysis (PCA) and the improved VGG16 model (a pre-trained 16-layer neural network model) to enhance the accuracy of HAR under sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…11. Note that the classification accuracy of our simulationbased HAR system is similar to today's real or experimentalbased HAR systems [21], [53], [54]. However, the proposed simulation-based approach is quite unique in that it effortlessly generates a large amount of high-quality simulation data for training purposes.…”
Section: Testing Of the Simulation-based Har System Employing Modelmentioning
confidence: 68%
“…11. Note that the classification accuracy of our simulationbased HAR system is similar to today's real or experimentalbased HAR systems [21], [53], [54]. However, the proposed simulation-based approach is quite unique in that it effortlessly generates a large amount of high-quality simulation data for training purposes.…”
Section: Testing Of the Simulation-based Har System Employing Modelmentioning
confidence: 68%
“…A study on a carpet system displayed its ability to use surface force information for 3D human pose analysis but revealed limitations in detecting certain body positions and differentiating similar movements [ 39 ]. Recently, radar-based HAR has gained interest due to its ease of deployment in diverse environments, insensitivity to ambient lighting conditions, and maintaining user privacy [ 18 , 40 ].…”
Section: Human Activity Recognition Approaches and Related Workmentioning
confidence: 99%
“…6) Fusion of radar and camera shows better precision in comparison to radar and camera alone [119]. 7) Efficient algorithms can decrease need of having big dataset: Using FMCW radar, Zhao et al [103] reported that the efficient algorithms can decrease the required data samples for training purpose. With an improved PCA, dimensional reduction is performed and a modified version of VGG net is used on the dataset provided by [81].…”
Section: B Human Activity Recognitionmentioning
confidence: 99%
“…11) The performance of shallow learning models (SVM in particular), degrades when training and test is performed in separate environment whereas DL model shows consistent performance [194]. 12) Using FMCW radar, Zhao et al [103] reported that efficient algorithms can decrease the required data samples for training purposes. 13) It has also been observed that efficient features extraction scheme and classifier can reduce the need of having big dataset [103].…”
Section: B Human Activity Recognitionmentioning
confidence: 99%